2020
DOI: 10.1371/journal.pone.0236797
|View full text |Cite
|
Sign up to set email alerts
|

Community pharmacists’ knowledge, perceptions, and practices about topical corticosteroid counseling: A real-world cross-sectional survey and focus group discussions in Korea

Abstract: Topical corticosteroids (TCs) are widely used to treat dermatological conditions such as eczema and psoriasis. It can be a safe and effective treatment when used appropriately. However, misguided information and corticosteroid phobia appear to contribute to inadequate adherence to therapy, leading to unsatisfactory treatment outcomes. Therefore, community pharmacists (CPs) are in a prime position to inform patients about the appropriate use of medicine. The aim of this study was to examine how the knowledge an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…In addition, other training pharmacy programs have shown to be effective in improving pharmacy staffs' knowledge and skills with positive impact on patient outcomes [23][24][25][26]. Kang et al [27] showed that an increase in community pharmacists' knowledge level about topical corticosteroids positively associated the quality of practice.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other training pharmacy programs have shown to be effective in improving pharmacy staffs' knowledge and skills with positive impact on patient outcomes [23][24][25][26]. Kang et al [27] showed that an increase in community pharmacists' knowledge level about topical corticosteroids positively associated the quality of practice.…”
Section: Discussionmentioning
confidence: 99%
“…low level of patients counseling may be due to lack of information or time, the patients feel negatively about topical glucocorticoids or/and the physicians feel negatively about the counseling for topical glucocorticoids by the pharmacists. Min Jung Kang et al found that bad feeling and physicians attitude was the most barrier for counseling (9) .…”
Section: Majority Of Mometasone Prescriptions Has Beenmentioning
confidence: 99%
“…Usually Iraqi patient keeps the prescription after being dispensed to refill it again with or without medical supervision which may encourage drug abuse or misuse (8) . Low level of patients counseling and education or insufficient knowledge of healthcare providers decrease patients adherence and awareness about the side effect of glucocorticoids (9) (10) .…”
Section: Introductionmentioning
confidence: 99%
“…One major topic of interest in recent years has been the use of antibiotics [ 21 , 22 , 23 ], especially in treating flu symptoms and colds. One common framework, as well as its variations, that has been used in the study of antibiotics use is the Knowledge–Perception–Practice (KPP) approach, which assesses what is known, believed and done about self-medication, capturing both cognitive and non-cognitive aspects relevant for self-medication behavior [ 24 ]. The main assumption underlying the model is that, by altering knowledge and perception, practices can be changed [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is a currently little work on possible predictors of general self-medication practices beyond research on choices for specific medications (e.g., antibiotics). Furthermore, the available research has reported differences across European countries and a relative lack of studies in Eastern European countries such as Romania [ 22 , 23 , 24 ]. Our study aimed to contribute to the literature by investigating views on self-medication practices in Romania.…”
Section: Introductionmentioning
confidence: 99%